Illocutionary Acts In The 2024 ABC News Presidential Debate Between Harris And Trump: A Pragmatic Study - Silfia Pratika (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2025)
This research aims to analyze the use of illocutionary acts in the 2024 U.S. presidential debate between Kamala Harris and Donald Trump, focusing on how the candidates employ language strategically to influence public perception. Grounded in Searle’s (1979) speech act theory, which builds upon the foundational work of Austin (1962), the study investigates five categories of illocutionary acts: assertive, commissive, declarative, expressive, and directive. Using a qualitative descriptive method, data were collected from the official transcript of the debate and analyzed through categorization and contextual interpretation (Yule, 1996; Thomas, 1995). The results reveal that assertive acts dominate the discourse, reflecting the candidates' efforts to build credibility and assert policy achievements or critiques. Commissive acts were used to make promises and show future commitments, while directive acts served to challenge opponents. Expressive and declarative acts helped shape emotional connections and formal policy stances. These findings demonstrate how each candidate constructs political narratives through language use, reinforcing Mey’s (2001) view that pragmatics involves understanding meaning within sociopolitical interaction. The study offers insights into the persuasive power of language in political communication and contributes to the broader field of pragmatic analysis. By synthesizing these frameworks, this study underscores the role of speech acts in crafting political narratives, shaping public perception, and advancing political communication research. Kata Kunci: illocutionary acts, assertive, commissive, declarative, expressive, directive